Flexible data line for improving EMC electromagnetic compatibility and preparation method thereof
By using the structure of a flexible soft magnetic cladding layer and an outer sheath layer in the data line, and using magnetic field orientation technology to adjust the easy magnetization axis, the problem of difficult to improve the magnetic permeability and shielding effect in high-frequency electromagnetic environments is solved, and the efficient electromagnetic compatibility and production efficiency of the data line are achieved.
Patent Information
- Application Number
- CN202510079927.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-18
AI Technical Summary
The prior art is difficult to improve the magnetic permeability and electromagnetic shielding effect of the data line in a high-frequency electromagnetic environment, and the extrusion molding of sheet magnetic powder is likely to cause cracking of the wire, limiting the improvement of magnetic properties.
A data line structure is adopted that includes a closely connected flexible covering, a flexible soft magnetic coating layer in the middle and a flexible outer sheath layer in sequence from the inside to the outside. The flexible soft magnetic coating layer in the middle is a composite material layer in which part or all of the sheet-shaped soft magnetic powder is evenly distributed in the matrix component containing the additive, and the direction of the easy magnetization axis is adjusted through the magnetic field orientation process in the long straight spiral tube to improve magnetic permeability.
In an electromagnetic environment of 200KHz~20GHz, the shielding efficiency of the data line is significantly improved, ensuring the flexibility and mechanical strength of the data line, and achieving efficient production efficiency.
Smart Images

Figure CN119811776A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a flexible soft magnetic wire, and in particular to a flexible data line for improving EMC electromagnetic compatibility and a preparation method thereof. Background Art
[0002] The electric field shielding of the existing data line can be achieved by a metal braided layer, a metal foil layer, and a single grounding method. The electromagnetic field interference can be reduced by twisted pair, soft ferrite magnetic ring, soft magnetic coating, and winding with a film coated with soft magnetic. Each method has its own advantages in terms of mechanical strength, service life, flexibility, production efficiency, and electromagnetic compatibility at different frequencies. It is much more difficult to improve the shielding effect of non-static magnetic fields and high-frequency electromagnetic fields. Theoretical studies have shown that the high-frequency magnetic properties of soft magnetic powders used in soft magnetic composite materials currently produced and widely used all comply with the Snoek limit, which is expressed by the following formula 1: (Formula 1) Where μi is the starting magnetic permeability, fr is the natural resonance frequency (or cutoff frequency), γ' is the gyromagnetic ratio, and Ms is the saturation magnetic induction intensity. Due to the limitation of the Snoek limit, the current working frequency of soft magnetic composite materials can only be below 100KHz-200KHz. With the increase of electromagnetic frequency, the magnetic permeability decreases inversely, which hinders the application of soft magnetic composite materials in the field of high-frequency microwaves. However, the spectrum from radio spectrum to microwave covers 3KHz~300GHz. The EMC electromagnetic compatibility of electrical equipment in the electromagnetic field environment becomes more and more difficult with the increase of magnetic field frequency. This poses a higher challenge to the satisfaction of EMC electromagnetic compatibility of data cables: How to obtain the ideal magnetic permeability and shielding effectiveness of the data cable against the electromagnetic field in the 200KHz~20GHZ electromagnetic environment; For the same flaky soft magnetic powder, if the sintering process is adopted, the magnet powder content is high, the density is high, and the magnetic permeability is also high, but the rigidity of the sintered magnet will restrict the flexibility of the wire; if the calendering process is adopted, the mechanical method of rolling helps the flaky powder to be arranged neatly, the powder filling amount can be increased, and the magnetic properties of the composite magnet can be relatively improved, but the calendering process cannot be directly used for wire forming; for the extruded data cable, the higher the powder filling amount is when the flaky magnetic powder is used as the modified filler, the easier it is for the wire to crack, and the increase in powder filling amount and density is limited. While meeting the balance between the mechanical strength and flexibility of the data cable, the improvement of the magnetic properties of the wire is restricted; Publication number: CN118440435A, polypropylene semi-conductive shielding material and its preparation method and application, discloses a polypropylene semi-conductive shielding material, characterized in that its raw materials include the following components by weight: 65-75 parts of polypropylene base material and elastomer base material, 20-30 parts of conductive carbon black and 3-8 parts of functional additives; the elastomer base material includes ethylene propylene diene monomer rubber; the weight ratio of the polypropylene base material to the elastomer is 1: (0.5-1); the functional additives include antioxidants, lubricants and dispersants. By adjusting the conductive carbon black to be evenly distributed in the polypropylene phase, not only the permeation threshold of carbon black is reduced, but also the shielding material obtains balanced mechanical properties and surface finish, and the tensile strength, elongation at break and conductivity of the polypropylene semi-conductive shielding material can be improved, and the polypropylene semi-conductive shielding can be effectively optimized. However, it does not involve any improvement in the EMC compatibility of electrical equipment in dynamic electromagnetic interference, especially high-frequency electromagnetic environments; Publication number: CN113674921A, a method for preparing a magnetically attracted, automatically curled and freely stretched data cable, which ensures the location and method of magnetic attraction of the wire from the physical shape, so that the data cable can be maintained in a curled magnetic state, and the stretching action is smooth, reflecting a new trend of magnetic absorption of the wire. This technical solution utilizes the surface magnetism and magnetic adsorption force of permanent magnetic materials, and has nothing to do with the high or low magnetic permeability and the realization of EMC electromagnetic compatibility of the data cable in a high-frequency electromagnetic environment. Summary of the invention
[0003] This technical solution helps to solve at least one of the following pain points: in a high-frequency electromagnetic environment, the magnetic permeability follows the Snoek limit, and as the frequency increases, the magnetic permeability decreases in the opposite direction, and the electromagnetic shielding effect is challenged; the extrusion molding of flaky magnetic powder makes the wire easy to crack, and under the premise of meeting the mechanical strength of the data line such as flexibility, the powder content cannot be increased, and the improvement of soft magnetic properties is limited.
[0004] According to some embodiments, a flexible data cable for improving EMC electromagnetic compatibility includes, from the inside to the outside, a tightly connected flexible coating on the core, a flexible soft magnetic coating layer in the middle, and a flexible outer sheath layer on the outside, wherein the flexible soft magnetic coating layer in the middle is a composite material layer in which part or all of the soft magnetic powder in the form of flakes is evenly distributed in a matrix component containing an additive, and part or all of the easy magnetization axis in the flexible soft magnetic coating layer is oriented along the axial circumference of the data cable; In some embodiments, the easy magnetization axis of at least part of the single crystals in the partially or entirely flaky soft magnetic powder is oriented along the axial circumference of the data line, and the volume of the hard magnetization axis portion becomes smaller; In some embodiments, the effective area of the axial circumferential surface of the soft magnetic powder that is partially or entirely in sheet form is greater than the effective area of the circumferential radial surface; In some embodiments, the effective area refers to the projected area; In some embodiments, the orientation degree of some or all of the easy magnetization axes in the flexible soft magnetic coating layer along the axial circumference of the data line is greater than the orientation degree along the circumferential radial surface; In some embodiments, the flaky soft magnetic powder has an aspect ratio greater than 1, preferably 25 to 200, and more preferably 50 to 100; In some embodiments, the flaky soft magnetic powder has a median particle size D50 of 2 to 840 μm, preferably 20 to 160 μm, and more preferably 47 to 84 μm; In some embodiments, the flaky soft magnetic powder has a weight specific surface area of 10 to 1590 m2 / kg, preferably 40 to 300 m2 / kg, and more preferably 86 to 159 m2 / kg; In some embodiments, the shielding effectiveness of the data line is equal to or greater than 20 dB at a frequency of 6.10G to 17.24 GHz; In some embodiments, the flexible outer layer of the data line is at least one of an electrically insulating plastic layer, a braided layer, and a leather decorative layer; In some embodiments, the data line diameter is 2.0-11.684 mm; In some embodiments, the data line diameter is 2.0-5.0 mm, wherein the thickness of the soft magnetic coating layer is 0.2-0.7 mm; In some embodiments, the flaky soft magnetic powder is one or more of the following materials: Fe, carbonyl iron, Mn-Zn ferrite, Ni-Zn ferrite, an alloy formed by Fe and at least one of Co and Ni, FeSiAl, FeNiMo, R2(Fe,Ni,Si,Al)17N3 (wherein R is Y, Ce, Nd or Pr), Sm2(Fe,Ni,Co)14B, R2(Co,Fe,Ni)17 (wherein R is Y or Nd); In some embodiments, the matrix component is an insulating high molecular polymer; In some embodiments, the insulating polymer includes at least one of a thermoplastic resin, a thermosetting resin, and a synthetic rubber; In some embodiments, the data line includes a cross-sectional shape of one of circular, flat, elliptical, axisymmetric regular shapes or any irregular shape; In some embodiments, the data cable connector is one of a USB type-c data connector, a lightning data connector, and an audio data connector.
[0005] According to some embodiments, the preparation method of a flexible data line for improving EMC electromagnetic compatibility comprises: step 1: preparation of a sheet of soft magnetic powder; step 2: granulation: the sheet of soft magnetic powder, binder, and processing aid are proportioned, fully mixed and refined, or the sheet of soft magnetic powder is coated and modified by a coupling agent, and then mixed with a binder and a processing aid, and then made into soft magnetic coating layer granules; step 3: extrusion molding and sheet orientation: the granules prepared above are mixed and plasticized and passed through the same die of the extruder with the coated material, and the coated material is extruded on the core, The semi-finished product of the flexible data line with the soft magnetic coating layer on the outside, while flowing and extruding, the flaky soft magnetic powder dispersed in the adhesive in the viscous flow state adjusts the force-bearing surface under the combined force of the shear force of the inner wall of the barrel and the outer wall of the coated object, the viscosity of the adhesive, and the driving pressure of the screw rotation, so that part or all of the flaky physical surfaces are arranged along the axial circumference to form an orientation along the axial circumference of the data line; Step 4: Add a flexible outer sheath: After cooling and solidification, braid a flexible electrical insulating outer sheath layer, or the flexible outer sheath layer is an electrical insulating plastic layer, which is co-extruded sequentially or synchronously with step 3; In some embodiments, the method for preparing the flaky soft magnetic powder includes the following process flow: smelting, ingot casting, crushing, ball milling, screening, annealing, batching, raw powder, flaking, drying, heat treatment, air separation, batching, and finished product; In some embodiments, the flexible data line is magnetized in an orientation in a long straight spiral tube, the direction of the magnetic field in the spiral tube is parallel to the axial direction of the data line, and part or all of the easy magnetization axes of the soft magnetic powder are oriented along the axial circumference of the data line; In some embodiments, the temperature of the magnetization orientation process is maintained at the polymer viscosity flow temperature; In some embodiments, the magnetization orientation process is maintained until the polymer is cooled and solidified; In some embodiments, the magnetic field size in the long straight spiral tube is at least 1.5 times, preferably 3-5 times, greater than the intrinsic coercivity Hcj of the soft magnetic powder; In some embodiments, the magnetic field in the long straight spiral tube is a constant current field, or a pulsed magnetic field performed multiple times. Beneficial Effects
[0006] 1. The axial and circumferential orientation of the flake physical surface of the soft magnetic powder during extrusion molding, the axial and circumferential orientation of the easy magnetization axis of the data line after magnetization, the orientation is based on the combination and superposition of axial + circumferential, macroscopic morphology + microscopic easy magnetization axis, increasing the coverage and density of the axial circumferential surface of the data line, and strengthening the contribution of magnetic permeability. In the electromagnetic environment of 200KHz~20GHZ, the shielding effectiveness of the data line is improved; 2. The temperature of the magnetization orientation process is maintained in the polymer viscous flow state, and the soft magnetic composite material layer is in the viscous flow state, the coercive force and viscosity are reduced, and in the parallel axial constant or multiple pulse magnetic fields in the long straight spiral tube, more easy magnetization axes in the soft magnetic powder are oriented to the maximum on the axial surface of the data line, and it is possible to improve the overall axial surface permeability of the data line; after cooling, the mechanical orientation of the morphology and the orientation direction of the easy magnetization axis are maintained, the utilization of the axial surface permeability can be superimposed, and the implementation of mass production and efficient production becomes possible; 3. The morphology and easy magnetization orientation of the flaky powder are both on the axial circumferential surface, so that the magnetic powder content prepared according to the proportion of the technical solution can be maximized. The data cable after extrusion meets the mechanical strength of the overall flexibility without cracking, and the EMC electromagnetic compatibility is improved at the same time. The structure and preparation method of the technical solution are also suitable for USB data cables, charging cables, audio cables, video cables, HDMI high-definition data cables, coaxial cables, etc. with wire diameters of 5-11.684mm and other specifications. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 : Schematic diagram of the magnetic field orientation structure of the data line in a long straight spiral tube; Among them, 10 flexible data lines, 20 long straight spiral tubes for magnetization, and 30 magnetic field line distribution; Figure 2 : Schematic diagram of the flexible data line structure; Among them, 11 is a flexible coated layer, 12 is a flexible soft magnetic coating layer, 13 is an outer sheath layer; 10a is an axial direction, 10b is a circumferential direction, 10c is a radial surface, and 10d is a circumferential surface; Figure 3-1 : Electron microscopic image of the sheet-like Sendust 3H powder used for the soft magnetic layer of the flexible data line in Example 1; Figure 3-2 : Electron microscopic image of the sheet-like Sendust 1H powder used for the soft magnetic layer of the flexible data line in Example 2; Figure 3-3 : Electron microscopic image of the sheet-like Sendust 2H powder used for the soft magnetic layer of the flexible data line in Example 3; Figure 3-4 : Electron microscopic image of non-flaky sendust powder used for the soft magnetic layer of the flexible data line of Comparative Example 1; Figure 4-1 : The test results of the relationship between the magnetic permeability and frequency of the 3H powder ring sample with a powder content of 83.3% in Example 1; Figure 4-2 : The test results of the relationship between the magnetic permeability and frequency of the 1H powder ring sample with a powder content of 83.3% in Example 2; Figure 4-3 : Test results of the relationship between magnetic permeability and frequency of a 2H ring powder sample with a powder content of 83.3% for Example 3; Figure 5-1: The shielding effectiveness test results of 9 samples of the soft magnetic material composite material layer of Example 1 with a powder content of 83.3% and a width of 1-9 cm respectively; Figure 5-2 : The shielding effectiveness test results of 9 samples of the soft magnetic material composite material layer of Example 2 with a powder content of 83.3% and a width of 1-9 cm respectively; Figure 5-3 : The shielding effectiveness test results of 9 samples of the soft magnetic material composite material layer of Example 3 with a powder content of 83.3% and a width of 1-9 cm respectively; Figure 5-4 : The shielding effectiveness test results of four samples of the soft magnetic material composite material layer of Comparative Example 1, with a powder content of 83.3% and a width of 1-4 cm respectively; Figure 6-1 : Schematic top view of the shielding effectiveness test sample and fixture structure; Figure 6-2 : Schematic diagram of shielding effectiveness detection structure; Among them, 40 test fixture and sample, 41 microstrip line, 42a signal input port, 42b signal output port, 43 tested sample, 50 signal line, 60 vector network analyzer.
[0008] The following is a further description of the specific implementation of the technical solution in conjunction with the accompanying drawings and specific embodiments. First, the relevant technical points involved in the specification are explained as follows: The temperature of the magnetization orientation process is adjusted according to the softening point of the adhesive actually used, and the heating time is controlled by the peripheral heating equipment to achieve the viscous flow state of the matrix component; The magnitude of the magnetic field is such that the orientation is fully saturated and the orientation and cooling and solidification are coordinated as synchronously as possible; The direction of the magnetic field in the spiral tube is parallel to the axis of the data line, allowing for engineering errors; The easy magnetization axis means that each magnetic powder contains at least one easy magnetization axis, and during the molding and magnetic field orientation process, as many easy magnetization axes as possible in each magnetic powder are oriented and maintained as required; The thickness of the soft magnetic layer of the data line is not an exact value, and uneven thickness during the molding process is allowed; Reference Figure 1 : Oriented magnetization in the long straight spiral tube 20: The solenoid is a three-dimensional coil, which is a single or multiple winding wire. The inside of the winding is hollow. When a current I (A) passes through a hollow solenoid 20 with a total length of l (m) and a number of turns N, a magnetic field with a magnetic field line distribution 30 will be generated inside. The magnitude of the magnetic field can be adjusted. μ0 is the vacuum magnetic permeability, n is the number of turns per unit length of the coil, and the magnetic induction intensity of a finite length straight solenoid is: or (Formula 2) Reference Figure 2 : Axial direction 10a: the length direction of the central axis of the data line, also the long axis direction; Circumferential direction 10b: the direction of the tangent or arc line at any point on the circumference of a circle with different radii and with any point on the long axis as the center; Radial surface 10c: i.e. radial surface, a cross section perpendicular to the axial direction of the data line, with any point of the long axis as the center; Peripheral surface 10d: a collection of axial side surfaces of cylinders with different radii with any point of the long axis of the data line as the center; Flexible sheath 11: includes a single wire or twisted pair of wires with a single flexible function or multiple functions such as flame retardancy and insulation, such as at least one power line, ground line, signal line, etc.; Soft magnetism: materials with low coercivity and high magnetic permeability; EMC stands for "electromagnetic compatibility", which refers to the ability of the electromagnetic energy generated by the data line to neither interfere with other devices nor be interfered by the electromagnetic energy of other devices; Reference Figure 5-1 , 5-2 、5-3、5-4: Shielding effectiveness: In the absence of a shield, the field strength of the radiation interference source transmitted to a certain point in space (P) is E1 (H1); after adding a shield, the field strength of the radiation interference source transmitted to the same point in space (P) is E2 (H2). Shielding effectiveness is the ratio of the two field strengths, expressed in dB (decibels) (dB) (Formula 3) The detection method used in this application is a dual-port microstrip line method. For extruded samples of flaky magnetic powder and non-flaky powder, which have the same content of 83.3%, and are named 1H powder, 2H powder, 3H powder, respectively, and different widths of 1 to 9 cm, the embodiment and comparative example samples are placed on the fixture microstrip line, and the frequency is 0.1 to 20 GHz. The shielding effectiveness and frequency relationship diagram under the same conditions are obtained by the vector network analyzer N5247A; Reference Figure 6-1 and 6-2 : The two-port microstrip line test fixture has a characteristic impedance of 50Ω, a distance of 7cm between the two ports, and a width range of 1-9cm for the sample under test. The fixture is excellent, and the measurement is verified by a vector network analyzer calibrated by OSI T. For further information, please refer to the article "Study on the Shielding Effectiveness of Carbonyl Iron Composite Materials Using the Two-Port Microstrip Line Method". DETAILED DESCRIPTION
[0009] Reference Figure 2 A flexible data cable 10 for improving EMC electromagnetic compatibility comprises, from the inside to the outside, a tightly connected flexible coating 11 in the core, a flexible soft magnetic coating layer 12 in the middle and a flexible outer sheath layer 13 on the outside, wherein the data cable flexible soft magnetic coating layer is a composite material layer in which part or all of the soft magnetic powder in the form of flakes is evenly distributed in a matrix component containing an additive, and the density is 2.53-2.95 g / cm3; In specific embodiments 1, 2, and 3, the flaky soft magnetic powder uniformly distributed in the matrix component containing the auxiliary agent of the flexible data line composite material layer is FeSiAl powder, and its mass percentage is 9.4% silicon, 5.6% aluminum, and the balance is iron; the flaky soft magnetic powder has a diameter-to-thickness ratio of 50-100, and is named 3H powder, 1H powder, and 2H powder, respectively. The particle size distribution is recorded in Table 1, and the powder scanning electron microscopy shows Figure 3-1 , Figure 3-2 , Figure 3-3 ; The preparation method of the flaky soft magnetic FeSiAl powder comprises: smelting, ingot casting, crushing, ball milling, screening, annealing, batching, raw powder, flaking, drying, heat treatment, air separation, batching, and finished product;
[0010] In specific embodiments 1, 2, and 3, there are three different formulation examples, and the percentages of the soft magnetic powder FeSiAl, adhesive, and additives uniformly distributed in the composite material layer of the soft magnetic coating layer of the flexible data line are respectively recorded in Table 2; the hardness and density of the flexible soft magnetic coating layer in the middle of the corresponding extruded data line are also respectively recorded in Table 2; Furthermore, there are also 3 examples of wire diameter size of the extruded flexible data cable corresponding to each formula example, so each embodiment has 9 samples, a total of 27 samples, and the sample numbers and corresponding meter weights are recorded in Table 2; the wire diameter size in Table 2 includes the 60W flexible coating of 5 cores and the flexible soft magnetic coating layer in the middle, and the meter weight is the weight of a length of 1m;
[0011] The flexible outer layer of the data cables of the 27 samples in Table 2 is at least one of an electrically insulating plastic layer, a braided layer, and a leather decorative layer; the data cable diameter surface shape is circular, and the data bus diameter is the wire diameter in the table plus the wire diameter of the flexible outer layer, wherein one of the bus diameters has an outer diameter of 5 mm; The binder of the composite material layer of the 27 samples of flexible data linear data lines in Table 2 is TPE, and the processing aid is at least one of a lubricant, an antioxidant, a coupling agent, a flame retardant, and a dispersant. The wire diameter recorded in Table 2 is a 60W flexible coating including 5 cores, so the actual thickness of the flexible soft magnetic coating layer varies, ranging from 0.2 to 0.7 mm; According to the relevant functions of the flexible coating on the core, the 27 sample data cable connectors in Table 2 are one of USB type-c data connectors, lightning data connectors, and audio data connectors.
[0012] A method for preparing a flexible data cable for improving EMC electromagnetic compatibility described in the 27 sample examples of Examples 1, 2, and 3 comprises: Step 1: Preparation of flaky soft magnetic powder iron silicon aluminum, taking weight percentages of 9.4 silicon, 5.6 aluminum, and the remainder iron for smelting, ingot casting, crushing, ball milling, screening, annealing, batching, raw powder, flaking, drying, heat treatment, risk, batching, and 1H, 2H, and 3H flaky soft magnetic powders recorded in Table 1; Step 2: Prepare materials according to the formula ratio in Table 2 and the above ingredients, fully mix and refine the rubber to prepare soft magnetic coating layer granules A; Step 3 Extrusion molding and morphology orientation: Mix the granules prepared above and plasticize them with the 5-core 60W quilt The coating is extruded through the same die of the extruder to extrude a semi-finished flexible data line with the coated material in the core and the soft magnetic coating layer on the outside. The temperature of the extrusion process is maintained at 180-220°C. During the flow extrusion, the flaky soft magnetic powder dispersed in the viscous flow binder is subjected to the combined force of the shear force of the inner wall of the barrel and the outer wall of the coated material, the viscosity of the binder in all directions, and the forward pressure of the screw rotation drive. Part or all of the flaky soft magnetic powder adjusts the magnetic powder force surface, and the flaky physical surface is arranged along the axial circumference to form an orientation along the axial circumference of the data line; Step 4: Adding an outer sheath: After cooling and solidification, a flexible outer sheath layer is braided, or the flexible outer sheath layer is a plastic layer, which is co-extruded synchronously with step 3; Reference Figure 1 In the 27 sample examples, the semi-finished product 10 of the flexible data cable with 5 cores and 60 watts, with the coating on the core and the soft magnetic coating on the outside, or the finished product 10 of the data cable with the outer sheath, is magnetized in a long straight spiral tube 20, the direction of the magnetic field in the spiral tube is parallel to the axial direction of the data cable, the temperature of the magnetization process is maintained at 120-180°C, the magnetic field size is 3000-5000Oe, and part or all of its easy magnetization axis is oriented along the axial circumference of the data cable; In the 27 sample examples, the middle flexible soft magnetic coating layer is a composite material layer in which part or all of the flaky FeSiAl soft magnetic powder is uniformly distributed in a matrix component containing an additive, and part or all of the easy magnetization axis in the flexible soft magnetic coating layer is oriented along the axial circumferential surface of the data line; part or all of the flaky physical surfaces of the soft magnetic powder that is part or all flaky are oriented along the axial circumferential surface of the data line, and the effective area of the soft magnetic powder that is part or all flaky along the axial circumferential surface is greater than the effective area of the circumferential radial surface; the orientation degree of part or all of the easy magnetization axis in the flexible soft magnetic coating layer along the axial circumferential surface of the data line is greater than the orientation degree of the circumferential radial surface; the flexible soft magnetic composite material layer in the middle of the 27 sample data lines has no cracks; Comparative Example 1: The difference from Example 1 is that the data line flexible soft magnetic coating layer is a composite material layer in which commercially available non-flaky FeSiAl soft magnetic powder is evenly distributed in a matrix component containing an additive, and the ingredients are prepared in the same proportion as Example 1 in Table 2, with a powder content of 83.3%; Comparative Example 2: The difference from Example 1 is that the data line flexible soft magnetic coating layer is a composite material layer in which 3H is evenly distributed in a matrix component containing an additive, with a powder content of 87.3% and an adhesive of 11.8%; The flexible soft magnetic composite material layer in the middle of the formed data cable is cracked, and the data cable cannot be subsequently magnetized and oriented or covered with a flexible outer sheath layer;
[0013] A. Detection of the relationship between magnetic permeability and frequency: A sample with a powder content of 83% was selected from each of the three embodiments corresponding to 1H powder, 2H powder, and 3H powder for detection of magnetic permeability. The samples were all in annular shape, with a thickness of 0.3 mm and a size of Φ8.0 x Φ3.04 × 0.3 mm. The samples were all extruded, and the density and hardness were exactly the same as those of the flexible soft magnetic layer peeled off from the data cable. The measurement results are shown in the figure. Figure 4-1 , 4-2 , as shown in 4-3; Complex permeability recording and analysis: As the frequency increases from 1-10MHz, the real part μ' of the permeability of Examples 1, 2, and 3 is maintained at a height of 120-250, and the imaginary part μ" gradually increases. The real part μ' does not decrease unilaterally with the increase of frequency, but first increases and then decreases; when it exceeds 100MHz, the imaginary part and the real part of Examples 1 and 2 can still be maintained above 50; the permeability of the flexible soft magnetic composite material layer of the data line of the technical solution has broken through the limitation that the operating frequency of the prior art can only be in the range of 100KHz-200KHz. The three samples can still play the role of the real part and the imaginary part within 1000MHz, and can meet the requirements of the permeability size of EMC electromagnetic compatibility in a dynamic electromagnetic environment; B. Measurement of data line shielding effectiveness: The soft magnetic composite material layer of the 27 sample data lines in Table 2 was peeled off to become a flexible film. Due to the uneven thickness of the film, it was impossible to directly test it. During the test, the same extruded flexible composite material as the peeled off was used for year-on-year measurement. The test sample thickness was 0.4 mm, the length was 7 cm, the powder content was 83.3%, and the width was 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm, 7 cm, 8 cm, and 9 cm respectively. Nine year-on-year test samples of Examples 1, 2, and 3 were placed Figure 6-1On the fixture shown, a dual-port microstrip line method was used at a frequency of 0.1 to 20 GHz to perform year-on-year measurements. By using a vector network analyzer N5247A, 404 data were taken for each test sample, and shielding effectiveness results of 9 samples of each of the three embodiments were obtained, as shown in FIG. Figure 5-1 , 5-2, 5-3; Comparative Example 1 test sample widths were 1, 2, 3, 4 cm, shielding effectiveness test results are shown in Figure 5-4 As shown;
[0014] Shielding effectiveness recording and analysis: The shielding effectiveness of the 9 samples in Example 1 can reach or exceed 20dB from 6.1G to 17.24GHz, and the best effect occurs in samples 1, 6, 5, and 7. The average value of 404 results measured from 0.1G to 18GHz is 16.53dB; The shielding effectiveness of the 9 samples in Example 2 can reach or exceed 20dB from 6.81G to 16.43GHz, and the best effect occurs in samples 1, 4, 5, and 3. The average value of 404 results measured from 0.1G to 18GHz is 16.27dB; The shielding effectiveness of the 9 samples in Example 3 can reach or exceed 20dB from 7.13G to 17.15GHz, and the best effect occurs in samples 4, 2, 6, and 8, with an average value of 15.19dB from 0.1G to 18GHz; The average value of the four samples in comparative example 1 from 0.1G to 18GHz is 3.41, and the maximum value does not exceed 6; It can be seen that the shielding effectiveness of the data cable of the present technical solution has broken through the limitation that the current soft magnetic composite material can only work at a maximum frequency of 100KHz-200KHz, and is much higher than the test results of the four samples in comparative example 1. The EMC electromagnetic compatibility of the data cable is improved.
Claims
1. A flexible data cable for improving EMC electromagnetic compatibility, characterized in that it includes, from the inside to the outside, a tightly connected flexible coating on the core, a flexible soft magnetic coating layer in the middle, and a flexible outer sheath layer on the outside, wherein the flexible soft magnetic coating layer in the middle is a composite material layer in which part or all of the flaky soft magnetic powder is evenly distributed in a matrix component containing an additive, and part or all of the easy magnetization axis in the flexible soft magnetic coating layer is oriented along the axial circumference of the data cable.
2. A flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The effective area of the axial circumferential surface of the soft magnetic powder which is partially or entirely in the form of a sheet is larger than the effective area of the circumferential radial surface.
3. The flexible data cable for improving EMC electromagnetic compatibility according to any one of claims 1 or 2, characterized in that: The orientation degree of the easy magnetization axis of part or all of the flexible soft magnetic coating layer along the axial direction of the data line is greater than the orientation degree of the radial direction of the circumferential direction.
4. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The flaky soft magnetic powder has an aspect ratio of 25-200 and a median particle size D50 of 20-160 μm.
5. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The flexible outer layer of the data line is at least one of an electrically insulating plastic layer, a braided layer, and a leather decorative layer.
6. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The data line has a diameter of 2.0-5.0 mm, wherein the soft magnetic coating layer has a thickness of 0.2-0.7 mm and a density of 2.4-3.0 g / cm3.
7. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The soft magnetic material is one or more of the following materials: Fe, carbonyl iron, Mn-Zn ferrite, Ni-Zn ferrite, an alloy formed by Fe and at least one of Co and Ni, FeSiAl, and FeNiMo, R2(Fe,Ni,Si,Al)17N3, wherein R is Y, Ce, Nd or Pr, Sm2(Fe,Ni,Co)14B, R2(Co,Fe,Ni)17, wherein R is Y or Nd.
8. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The matrix component is an insulating high molecular polymer.
9. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The data line includes a cross-sectional shape of one of the regular axially symmetrical shapes such as circular, flat, and elliptical, or any irregular shape.
10. The flexible data cable for improving EMC electromagnetic compatibility according to claim 1, characterized in that: The data cable connector is one of a USB type-c data connector, a lightning data connector, and an audio data connector.
11. A method for preparing a flexible data cable for improving EMC electromagnetic compatibility according to any one of claims 1 to 10, characterized by comprising: Step 2: Preparation of a sheet of soft magnetic powder. Step 2: Granulation: proportion ingredients, flaky soft magnetic powder, binder, processing aid, fully mix and refine, or flaky soft magnetic powder is modified by coupling agent, and then mixed with binder and processing aid, and then made into flexible soft magnetic coating granules. Step 3: Extrusion molding and sheet orientation: mix and plasticize the granules prepared above and pass them through the same die of the extruder with the coated material to extrude the semi-finished flexible data line with the coated material in the core and the flexible soft magnetic coating layer on the outside. While flowing and extruding, the flaky soft magnetic powder dispersed in the viscous flow state binder adjusts the force-bearing surface under the combined action of the shear force of the inner wall of the barrel and the outer wall of the coated object, the viscosity of the binder, and the driving pressure of the screw rotation, so that part or all of the flaky physical surface is arranged along the axial circumference to form an orientation along the axial circumference of the data line; step four, adding a flexible outer sheath: after cooling and solidification, weaving an electrically insulating flexible outer sheath layer, or, the flexible outer sheath layer is an electrically insulating plastic layer, which is co-extruded simultaneously with step three or successively.
12. The method for preparing a flexible data cable for improving EMC electromagnetic compatibility according to claim 11, characterized in that: The preparation of the flaky soft magnetic powder includes the following process flow: smelting, ingot casting, crushing, ball milling, screening, annealing, batching, raw powder, flaking, drying, heat treatment, air separation, batching, and finished product.
13. The method for preparing a flexible data cable for improving EMC electromagnetic compatibility according to claim 11, characterized in that: The flexible data line is magnetized in an orientation in a long straight spiral tube, the magnetic field direction in the spiral tube is parallel to the axial direction of the data line, and the easy magnetization axis of part or all of the soft magnetic powder in the soft magnetic coating layer is oriented along the axial circumference of the data line.
Citation Information
Patent Citations
Polypropylene semiconductive shielding material as well as preparation method and application thereof
CN118440435A
Noise Suppression Cable
CN104851510A
Preparation method of data line capable of being automatically curled and freely stretched through magnetic attraction
CN113674921A
Method of manufacturing magnetic body, the magnetic body, and cable
JP2002198239A
Radiated electromagnetic wave suppressing cable and its manufacturing method
JP2005228694A